Recent Reflections on the Gospel according to Mark - Kealy, Sean P. (Biblical theology bulletin, 2005)
This article is an invitation to each reader to reflect on our journey through life with an amazingly deep work like the Gospel of Mark. Mark puts a radical question to our vision of life, the kind of God we believe in, the journey that that God invites—or better commands—us to make. As the poet said, it is above all an invitation to dance within the storm of life as Jesus once did for us.